Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2466251
|View full text |Cite
|
Sign up to set email alerts
|

Designing for perceptual crossing

Abstract: Perceptual crossing is the reciprocal interplay of perceiving while being perceived. In this paper we discuss the last iteration of our ongoing research project on designing for perceptive qualities in systems of interactive products. We describe the design of explorative behavior in an artifact to enable the artifact and a person to engage in perceptual crossing. The explorative behavior is compared to the following and active behavior, the results of two earlier iterations. Through the iterations we formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In our study, we identified five social vocabulary items ("Greeting, Hello, Thanks, Welcome, I see you seeing me") that were absent from Amazon Echo and Google Home. As the interactive device developed in [11] demonstrated, such social feedbacks could increase users' understanding and engagement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we identified five social vocabulary items ("Greeting, Hello, Thanks, Welcome, I see you seeing me") that were absent from Amazon Echo and Google Home. As the interactive device developed in [11] demonstrated, such social feedbacks could increase users' understanding and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The other interesting term I see you seeing me was mainly found in the human-robot interaction in Film #6 (e.g., 2:18-2:22). These designs help build perceptual crossing and engage users' involvement [11]. By utilizing this social vocabulary, designers can improve the design qualities of user-system interactions.…”
Section: Socializementioning
confidence: 99%
See 1 more Smart Citation
“…Such a lack of a prompt, or feedforward, represents a total decoupling of actions and functions. Deckers et al [10] proposed the concept of perceptual crossing to show the system's "face" and let users know their approach is acknowledged: a reciprocal interplay of perceiving while being perceived. With perceptual crossing, users can not only recognize the possibility to initiate interactions with machines but also engage in a more continuous way with something akin to an artificial living creature.…”
Section: Theoretical Backgroundmentioning
confidence: 99%